Nano-Based Drug Delivery or Targeting to Eradicate Bacteria for Infection Mitigation: A Review of Recent Advances - Yeh, Yuan-Chieh; Huang, Tse-Hung; Yang, Shih-Chun; Chen, Chin-Chang; Fang, Jia-You (Frontiers in Chemistry, 2020)
Pathogenic bacteria infection is a major public health problem due to the high morbidity and mortality rates, as well as the increased expenditure on patient management. Although there are several options for antimicrobial therapy, their efficacy is limited because of the occurrence of drug-resistant bacteria. Many conventional antibiotics have failed to show significant amelioration in overall survival of infectious patients. Nanomedicine for delivering antibiotics provides an opportunity to improve the efficiency of the antibacterial regimen. Nanosystems used for antibiotic delivery and targeting to infection sites render some benefits over conventional formulations, including increased solubility, enhanced stability, improved epithelium permeability and bioavailability, prolonged antibiotic half-life, tissue targeting, and minimal adverse effects. The nanocarriers’ sophisticated material engineering tailors the controllable physicochemical properties of the nanoparticles for bacterial targeting through passive or active targeting. In this review, we highlight the recent progress on the development of antibacterial nanoparticles loaded with antibiotics. We systematically introduce the concepts and amelioration mechanisms of the nanomedical techniques for bacterial eradication. Passive targeting by modulating the nanoparticle structure and the physicochemical properties is an option for efficient drug delivery to the bacteria. In addition, active targeting, such as magnetic hyperthermia induced by iron oxide nanoparticles, is another efficient way to deliver the drugs to the targeted site. The nanoparticles are also designed to respond to the change in environment pH or enzymes to trigger the release of the antibiotics. This article offers an overview of the benefits of antibacterial nanosystems for treating infectious diseases.